RAB6B is a potential prognostic marker and correlated with the remolding of tumor immune microenvironment in hepatocellular carcinoma - Peng, Hao; Zhu, Erwei; Wang, Jitao; Du, Xuanlong; Wang, Chonggao; Yang, Meng; Zhang, Yewei (Frontiers in Pharmacology, 2022)
Backgrounds: Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer and the second leading cause of death among all cancers. The Ras-associated binding (Rab) proteins constitute the largest family of the Ras superfamily of small GTPases, which mainly mediate membrane trafficking processes. RAB6B is a member of Rab GTPases, and it has been found to be dysregulated in various tumors. However, the clinical significance, correlations with immune cells, and stroma infiltration of RAB6B in HCC remain unclear. Methods: RAB6B mRNA and protein expression in HCC were examined using the TIMER, HCCDB, UALCAN, and HPA databases. The genetic alterations of RAB6B were analyzed by cBioPortal and COSMIC databases. The correlations between RAB6B and tumor-infiltrating immune cells and cancer-associated fibroblasts were explored by using TIMER, TISIDB, and GEPIA databases. Co-expression networks of RAB6B were investigated based on LinkedOmics. Drug sensitivity was analyzed through the GDSC and CTRP databases. RAB6B was knocked down with siRNA in HCC cell lines. EdU assay was performed to detect the cell proliferation ability, flow cytometry was used to compare the differences in the ability of apoptosis, and MTT was used to evaluate the drug sensitivity in vitro. Results: RAB6B mRNA and protein expression were upregulated in the HCC tissues. Kaplan–Meier and Cox regression analyses suggested that highly expressed RAB6B was an independent prognostic factor for poor survival in HCC patients. Moreover, we found that RAB6B expression was positively correlated with the infiltration of immune cells in HCC, including some immunosuppressive cells, chemokines, and receptors, meanwhile RAB6B expression was associated with CD8+T cells exhaustion, resulting in an immunosuppressive microenvironment. Additionally, functional enrichment analysis indicated that RAB6B may be involved in ECM remodeling in the TME, and RAB6B expression was positively associated with CAFs infiltration. Furthermore, RAB6B presented a positive association with sensitivity to GDSC and CTRP drugs. RAB6B knockdown inhibited the cell proliferation and promoted apoptosis and sensitivity to cisplatin of HCC cells in vitro. Conclusion: Our study revealed that RAB6B is a potential biomarker for poor prognosis in HCC patients and correlates with the formation of the immunosuppressive microenvironment in HCC.